Мова як виразник соціальної ідентичності: соціолінгвістичні маркери комунікації - Лисецька, Наталія Григорівна; Lysetska, Nataliia H. (Східноєвропейський національний університет імені Лесі Українки, 2016)
The article brings up a question of social markedness of speech in German-speaking communication. On the basis of theoretical works of such German scientists as R. Geißler, H. Löffler, Werner H. Veith et al., the trends of sociolinguistics as a science are shown, scientific literature on the social nature of language and on the interaction of language with external factors is examined. Basic models of structural differentiation of society are arranged based on external criteria and values guidelines. The dependence of linguistic markedness on social structure is shown. Attention is focused on “Code-switching”, i.e. the ability of the speaker to change his/her vocabulary if necessary, depending on where and among whom the process of communication is occurring. It is established that it is important for the speaker to learn to communicate in accordance with those regulatory requirements that correspond to the communication situation taking into consideration the time and place of occurrence of the interaction and the status of the interlocutors. Successful communication implies linguistic competence.
Language as an exponent of social identity: sociolinguistic markers of communication
Keywords: Соціолінгвістичні маркери комунікації; language competence; dichotomic; communication; social markedness of speech; social differentiation of society; the theory of linguistic deficit